Modern singing sons of the Pharaohs: Transcriptions and Orientalism in a Digital Coptic Music Collection - Ramzy, Carolyn (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2015)
In 2009, the U.S. Library of Congress officially launched the Ragheb Moftah Collection, an online exhibit that presented the largest music archive of Coptic liturgical recordings and music transcriptions outside of Egypt. Moftah, an amateur Egyptian collector, had commissioned an English composer, Ernest Newlandsmith, to notate and record the entire Orthodox hymnody. They both believed that, as the last connection to a Pharaonic and pre-Islamic past, the ancient melodies lay unchanged, “buried under a debris of Arabic and other ornamentation.” Drawing on Wendy Cheng’s notion of strategic orientalism (2013) and Timothy Mitchell’s staging modernity (2000), I explore contemporary discursive politics of sound archives in the Coptic community. Specifically, I investigate the role of Coptic music archives in articulations of community legitimacy, indigeneity, and agency as a religious and political minority in a Muslim majority nation. How have today’s cantors and activists rendered western transcriptions as sound objects which to negotiate authenticity as Egypt’s last remaining “modern sons of the pharaohs,” even without being able to read them? As the principal curator of the site, I explore how Western scholarly encounters have not only entangled Coptic music discourses in a western-centered teleology of modernity and progress, but in emulating the West, also infused them with orientalist critiques that equated heterophony and embellishments to “Arab debris” that marked signs of backwardness.